KONFLIK TANAH DI TENGAH PEMBANGUNAN - Josef Purnama Widyatmadja (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2017)
Economic development is a necessity in a nation longing for progress. But often the building also had its negative effects are not small. One of the adverse effects of development is the horizontal conflict due to land issues. Tension between economic interests with the interests of the people. It is often injured sense of justice. There were changes in the ownership status of previously communal land into private property. Weak community then became lost their land due to the construction process. The author tries to explain the issue of this land and give his view of how development should be implemented for the benefit of the people, especially the weak are not neglected.